THE CYTOKINE PROFILE CHANGES AND CONTENT ANTI-HSP60 ANTIBODY OF DIFFERENT SPECIFICITY IN PATIENTS WITH PERIODONTITIS - G.F. Biloklytska; O.V. Kopchak; A. M. Vorobiova (Український стоматологічний альманах, 2018)
Introduction. Periodontitis is considered as a multifactorial disease resulting from a combine impact of local and systemic factors on the background of altered reactivity. The stimulation of the immune system by periodontal bacteria results in the increased production of pro-inflammatory cytokines, which play an important role in the pathogenesis of the disease and is determined by activation of leukocytes, macrophages, fibroblasts and endothelial cells via nonspecific host response to infections, trauma, ischemia etc. The heat shock proteins are considered as an important antigen, which trigger this process. The quantitative characteristics and relationships between pro and anti-inflammatory cytokines (cytokine balance) reflect the dynamics of inflammation and correlate with activity of certain cardio-vascular diseases, infections and malignant tumors, allowing the objective estimation of the disease severity and prognosis. However the role of blood cytokines in periodontal disease is still a subject of debate in the literature.